Assessment and feasibility of the four landmarks of the aortic root in a cohort of very preterm infants - Sam Phillips; Koert A de Waal (Wolters Kluwer Medknow Publications, 2015)
Background : The diameter of the aortic root is used as a parameter to calculate blood flow in very preterm infants. There are considerable differences in diameter of the four anatomical landmarks of the aortic root in children and adults, but limited data are available for the very preterm population. The aim of this study was to obtain reference and reliability data on two-dimensional measurements of the aortic root in very preterm infants <30 weeks gestation. Materials and Methods : Fifty long axis echocardiograms were reviewed and re-analyzed for measurements at the four anatomical landmarks of the aortic root; the aortic annulus, sinus of Valsalva (SV), sinotubular junction, and the proximal ascending aorta (PAA). A subjective visual scoring system was developed to quantify image quality. A random sample of images was blindly re-measured to assess intra- and inter-observer reliability. Results : Significant differences in diameter were found between the four landmarks, except between SV and PAA. Inter-observer coefficients showed marginal variation ranging from 5.0% to 8.2%, with slightly lower intra-observer variability. Overall image quality score was poorest for PAA on standard long axis images but improved when the probe was adjusted along the outflow tract. Conclusion : We present reliability and reference values for all four anatomic landmarks of the aortic root in very preterm infants and demonstrated the importance of standardizing and reporting cardiac output measurements in preterm infants.